Decreased SMG7 expression associates with lupus-risk variants and elevated antinuclear antibody production - Deng, Yun (Ann Rheum Dis, 2016)
OBJECTIVES: Following up the SLE GWAS identification of NMNAT2 at rs2022013, we fine-mapped its 150kb flanking regions containing NMNAT2 and SMG7 in a 15,292 case-control multi-ancestry population and tested functions of identified variants. METHODS: We performed genotyping using custom array, imputation by IMPUTE 2.1.2, and allele specific functions using qRT-PCR and luciferase reporter transfections. SLE PBMCs were cultured with siRNAs to measure antinuclear antibody (ANA) and cyto/chemokine levels in supernatants using ELISA. RESULTS: We confirmed association at NMNAT2 in European American (EA) and Amerindian/Hispanic ancestries, and identified independent signal at SMG7 tagged by rs2702178 in EA only (P=2.4×10(−8), OR=1.23 [95%CI=1.14–1.32]). In complete linkage disequilibrium with rs2702178, rs2275675 in the promoter region robustly associated with SMG7 mRNA levels in multiple expression quantitative trait locus datasets. Its risk allele was dose-dependently associated with decreased SMG7 mRNA levels in PBMCs of 86 SLE patients and 119 controls (P=1.1×10(−3) and 6.8×10(−8), respectively) and conferred reduced transcription activity in transfected HEK-293 and Raji cells (P=0.0035 and 0.0037, respectively). As a critical component in the nonsense-mediated mRNA decay pathway, SMG7 could regulate autoantigens including RNP and Sm. We showed SMG7 mRNA levels in PBMCs correlated inversely with ANA titers of SLE patients (r=−0.31, P=0.01), and SMG7 knockdown increased levels of ANA IgG and CCL19 in SLE PBMCs (P=2.0×10(−5) and 2.0×10(−4), respectively). CONCLUSIONS: We confirmed NMNAT2 and identified independent SMG7 association with SLE. The inverse relationship between levels of the risk-allele associated SMG7 mRNAs and ANA suggested the novel contribution of mRNA surveillance pathway to SLE pathogenesis.